Exogenously Applied Trehalose Augments Cadmium Stress Tolerance and Yield of Mung Bean (Vigna radiata L.) Grown in Soil and Hydroponic Systems through Reducing Cd Uptake and Enhancing Photosynthetic Efficiency and Antioxidant Defense Systems - Sadia Rehman; Muhammad Umer Chattha; Imran Khan; Athar Mahmood; Muhammad Umair Hassan; Asma A. Al-Huqail; Mohamed Z. M. Salem; Hayssam M. Ali; Christophe Hano; Mohamed A. El-Esawi (Plants, 2022)
Cadmium (Cd) toxicity is a serious environmental issue causing a significant reduction in crop growth and productivity globally. Trehalose (Tre) has emerged as an important reducing sugar that can reduce the adverse impacts of different abiotic stresses. Therefore, the present investigation was performed to determine the key role of Tre in alleviating Cd stress in the mung bean (Vigna radiata L.) crop. The study was comprised of different treatments of cadmium (0, 10, 20 mg kg−1 soil) and Tre (0, 15 and 30 mM). Cd stress significantly restricted the growth and yield of mung bean. However, Tre supplementation markedly improved growth and yield due to pronounced reductions in Cd uptake and Cd-induced oxidative stress as shown by the lower production of hydrogen peroxide (H2O2), electrolyte leakage (EL) and malondialdehyde (MDA) in Cd-stressed plants as well as by the enhanced activities of antioxidant enzymes (CAT, POD, APX and AsA). Moreover, the ameliorative role of Tre to Cd toxicity was also demonstrated by its ability to enhance chlorophyll contents, total soluble protein (TSP) and free amino acids (FAA). Taken together, Tre supplementation played a key beneficial role in improving Cd stress tolerance and yield traits of mung bean through restricting Cd uptake and enhancing photosynthetic capacity, osmolytes biosynthesis and antioxidant activities.